Identification of sulfur-containing isoprenoids with non-adamantane cage structures in crude oil. (1st May 2023) - Wu, Jianxun; Zhang, Weilai; Wang, Yuanfeng; Zhang, Yahe; Shi, Quan
Graphical abstract: Highlights: A series of novel sulfur compounds were identified in the crude oil. The sulfur compounds have cage structure but not thiadiamondoids. The sulfides are likely derived from carotene by sulfur linkage of the isoprenoid. The formation of cage sulfides is relevant to BSR instead of TSR process. Abstract: We report here the identification of a series of novel, carotenoid-derived, non-thiadiamondoids cage organic sulfur compounds (OSCs) from the crude oil. Non-polar sulfur compounds were isolated from the crude oil by the methylation/demethylation method. Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) and gas chromatography-mass spectrometry (GC–MS) were used to characterize the separated OSCs. OSCs with cage structure were tentatively identified as 2-thiatricyclo[4.4.0.0 < 3.8 > ]decanes. The tail-to-tail linkage of the isoprenoid is the skeleton basis for the formation of these novel cage OSCs. Geochemical analysis and MS results indicate the direct generation of these cage OSCs by biological sulfate reduction instead of thermochemical sulfate reduction. The findings provide new molecular clues for the preservation of hydrocarbons in geological environments by sulfurization. The cage OSCs have the potential to act as biomarkers for the study of sedimentary environment.